PERENCANAAN DAN PELAKSANAAN KEGIATAN EKSTRAKURIKULER ROHANI ISLAM DALAM PEMBINAAN KARAKTER PESERTA DIDIK DI SMAN 02 MUKOMUKO - Dosi Marriyeni (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2016)
Planning extracurricular activities Rohani Islam in character building of students at SMAN 02 Mukomuko not run as ideally run a good organization and the superior, the weakness of planning in carrying out extra-curricular activities of the Soul of Islam in the Guidance Character of Students at SMAN 02 Mukomuko is the lack of preparation of teaching either syllabus, and lesson plan. The process of character building is done through an approach directly and indirectly, to the method used in the process of coaching is exemplary method, habituation, advice, punishment and reward and supported by religious activities in school. As for the supporting factors and obstacles in extracurricular activities Spiritual Islam is the support of the school principal to extracurricular activities, support of SMA Negeri 02 Mukomuko, and facilities without the means or place for religious activities in schools, it is incomplete. While the inhibiting factors in the implementation of extracurricular activities Rohis is the lack establish brotherhood with all SMA Negeri 02 Mukomuko, lack of attention to other teachers Rohis against religious activities, as well as the students' lack of awareness of the importance of knowledge of Islam.